(untitled) (Research, Society and Development, 2021)
Arbovirosis are diseases caused by arthropod-borne viruses and affect the region of the Americas, including the South American continent, where provoke impact on the economy and public health. Among the more than 500 viruses registered in the International Catalog of Arbovirus, those that cause dengue, zika fever and chikungunya stand out. Thus, this article comprises a descriptive study based on secondary data where we compare biological and diagnostic aspects these diseases, as well as assessing its presence, between 2015 and 2020, in the countries that integrate the su-american continental portion. Despite the considerable progress made in recent years to better understand the molecular aspects of etiologic agents and clinical conditions, the scenario is complex and the three arboviruses caused outbreaks in South America, in the period described, even in different proportions, with dengue remaining the most common arbovirus infection, whose the incidence rates fluctuate each analyzed year. The fight against arboviruses must be permanent and requires well-founded intersectoral policies and individual responsibility. Government interventions need to tighten up to implement measures to combat, and health and education systems could align more effectively for a stronger work to raise the awareness that is triggered from basic education students, helping in the continued education of the population in favor of a more oriented and prudent society. It is also necessary to reflect on the effectiveness of information systems to decrease the problem of underreporting that prevents showing the real scenario of these diseases.